Active and Unidirectional Acceleration of Biaryl Rotation by a Molecular Motor. (20th February 2020) - Uhl, Edgar; Mayer, Peter; Dube, Henry
Abstract: Light‐driven molecular motors possess immense potential as central driving units for future nanotechnology. Integration into larger molecular setups and transduction of their mechanical motions represents the current frontier of research. Herein we report on an integrated molecular machine setup allowing the transmission of potential energy from a motor unit onto a remote receiving entity. The setup consists of a motor unit connected covalently to a distant and sterically encumbered biaryl receiver. By action of the motor unit, single‐bond rotation of the receiver is strongly accelerated and forced to proceed unidirectionally. The transmitted potential energy is directly measured as the extent to which energy degeneration is lifted in the thermal atropisomerization of this biaryl. Energy degeneracy is reduced by more than 1.5 kcal mol −1, and rate accelerations of several orders of magnitude in terms of the rate constants are achieved. Abstract : Eine integrierte molekulare Maschine ermöglicht die Übertragung von potentieller Energie von einer Motoreinheit auf einen entfernten, kovalent gebundenen und sterisch stark abgeschirmten Biaryl‐Empfänger. Durch die Wirkung der Motoreinheit wird die Einfachbindungsrotation in der Empfängereinheit stark beschleunigt und kann nur unidirektional verlaufen.